Perceptions of online teaching and learning during the COVID-19 pandemic in Barbadian primary and secondary schools - Stuart, Kristina; Devonish, Dwayne; Babb, Unri; Burke, Kenroy; McClean-Trotman, Lisa (International Journal on Integrating Technology in Education (IJITE), 2021)
This paper explores a sample of data collected from a UNICEF Eastern Caribbean rapid assessment on teaching and learning during the COVID-19 pandemic in eight countries. The primary investigation method was mixed and captured data from key participants/stakeholders in education using CAPI Technology and Video Conferencing tools. Statistical analyses and qualitative thematic analysis were conducted to report on findings using Statistical Package for the Social Sciences and Nvivo Qualitative Software. The data on online teaching and learning from Barbados was selected for further review and presented an opportunity to assess the Barbadian experience against other developing and developed countries. In assessing these perceptions in a sample of primary and secondary schools, stakeholders were generally dissatisfied with the online and blended learning modalities citing challenges relating to the equality and equity in access to devices and the enabling environment that facilities effective online teaching and learning.
Keywords: online teaching; blended learning; COVID-19; education equity; teaching and learning